The Second Most Important Decision: Protocol for Partnering for Intern Placement - Hewitt, Kimberly Kappler; Rumley, Mark A. (Theory & Practice in Rural Education, 2022)
For principal preparation program success, the selection of an aspiring school administrator’s internship placement/mentor principal is second in importance only to the decision about whom to select into the program. In this article, we review the scant literature on internship placement assignment processes, none of which are specific to rural places. We then describe the Principal Preparation for Excellence and Equity in Rural Schools (PPEERS) program – a partnership of 12 rural districts and a large public university – and explain the process by which the partnership co-designed their internship placement protocol and Assignment of Internship Placements tool. We then introduce the protocol, which involves program leaders traveling to each rural partner district across a wide geographic area to meet with the superintendent and District Point Person – the cabinet-level administrator who is the lead district liaison for PPEERS – to consensually select a mentor principal/internship site for each Intern, using the internship tool, which identifies factors to select for and to avoid. After describing the protocol and introducing the tool, we outline our action research methods. Utilizing a two-phase reflective inquiry process, we drew on perceptions of leadership coaches, district partners, and program leaders to reflect on contextual considerations, the impact of the tool, and ways to improve our placement practice. Contextual considerations reflect realities of rural districts, including limited placement choices in small districts, limited number of principals who fit the mentor principal criteria, and micropolitical considerations. Improvements to our process include considering the entire leadership team of a school when selecting placements; including additions to the tool regarding consideration of equity, diversity, and inclusion, as well as addition of a “Goldilocks school” element; and ideas for increasing mentor principal readiness and intern knowledge of curriculum and pedagogy when placed in a school level that is unfamiliar to them. In these ways the partnership can leverage rural partner assets and address contextual challenges. We conclude with implications for rural school leader preparation programs.